Electrochemical and Surface Studies on the Passivation Behavior of Sputter-deposited W-Ni Alloys in NaOH Solutions - Bhattarai, J.; Sah, S. P.; Jha, H. (Journal of Nepal Chemical Society, 2007)
The passivation behavior of the sputter-deposited amorphous or/and nanocrystalline W-Ni alloys is studied in different concentrations of NaOH solutions at 25°C, open to air using corrosion tests, electrochemical measurements and confocal scanning laser microscopic (CSLM) techniques. The corrosion rates of the W-Ni alloys containing about 60-80 at% nickel are nearly two orders of magnitude lower than that of tungsten and even lower than that of nickel metal in 1 M NaOH solution at 25°C. The pitting corrosion is observed in the tungsten-rich W-9Ni alloy from CSLM studies. The open circuit potentials of all the examined W-Ni alloys are located between those of tungsten and nickel metals in 0.01, 0.1 and 1 M NaOH solutions. The stability of the passive films formed on the sputter-deposited W-Ni alloys increased with decreasing the concentrations of NaOH solutions. DOI: 10.3126/jncs.v22i0.517 Journal of Nepal Chemical Society Vol. 22, 2007 pp. 7-16